The Relationship Between Faculty Support, Academic Self-efficacy, Academic Emotions, and Online Learning Performance Among University Students in China - Mao Zhao; Siti Mistima Maat; Norzaini Azman; En Zheng (SAGE Open)
Online learning performance (OAP) serves as a critical determinant of educational quality and students’ academic success. In this study, we probe into the impact of faculty support (FS) on online learning performance among university students and assess the mediating roles of academic self-efficacy (ASE) and academic emotions (AE). A quantitative survey design was adopted, which involved public universities in Sichuan province in China. The participants consisted of 2,124 public university students who were selected via stratified sampling. Data were analyzed using partial least squares structural equation modelling (PLS-SEM) via Smart PLS 3.0 software. The analysis conducted using the standard bootstrapping procedure allowed for the estimation of both direct and indirect path coefficients in the study. Supported by the social support theory of faculty support, social cognitive theory of academic emotions, and self-efficacy theory of academic self-efficacy, Our results indicate that (1) a positive association between faculty support and students’ online learning performance, (2) the mediating effect of academic emotions between faculty support and online learning performance, and (3) the mediating effect of academic self-efficacy between faculty support and online learning performance. This study echoes prior research emphasizing faculty support as a pivotal component in enhancing student learning outcomes, while spotlighting the crucial role of academic self-efficacy and emotions in bolstering this relationship. This study, of noteworthy significance, foregrounds the importance of faculty support, academic self-efficacy, and academic emotions in optimizing online learning performance in higher education. Future research directions and implications are further discussed.